Moral Dilemmas in The War of Ethical Analysis Against Violations of Humanitarian Law by State and Non-State Actors - Yudha Irawan; Kamarulzaman bin Komaruddin; Tarsisius Susilo; Herlan Budi Hermawan; Anggit Budi Wibowo (International Journal Labs, 2025)
International Humanitarian Law (IHL) exists as a normative guide aimed at limiting suffering during armed conflict, especially by establishing rules on the protection of individuals who do not take part in combat, such as civilians, medical personnel, and prisoners of war. The purpose of this study is to identify the positive legal provisions that govern the legal issues under review, the legal principles or juridical principles that are relevant in analyzing the legal issues under study, and to determine the juridical interpretation of laws and regulations related to these legal issues. Normative legal research methods are used. The results of this study indicate that, with proper and consistent interpretation, humanitarian law can be internalized into the national legal system and become the basis for enforcing justice against offenders, as well as protecting victims from abuse of power and violence.